Responsible Literature Searching for Research: A Self-Paced Interactive Educational Program (Out of Print) - Charles Wessel (Association of American Medical Colleges, 2006)
Abstract The exponential growth of information resources mandates that researchers know how to use a broad array of print and electronic tools. Thus, we at the Health Sciences Library System at the University of Pittsburgh developed this self-paced interactive educational program to teach researchers the fundamentals of literature searching. The program provides a framework, instruction, and guidelines on the accepted practices and principles associated with the biomedical literature search process, as well as identification and use of major information resources, the role of reference librarians in the literature search process, the limitations of information resources, and determining what is an adequate literature search for topics such as drug safety and identification of adverse events. Learners can access the self-directed module by clicking on the attached link and following the directions. This program was developed with sponsorship by the Association of Academic Health Sciences Libraries with support from a cooperative agreement between the Association of American Medical Colleges and the Office of Research Integrity of the US Department of Health and Human Services. It has been assumed that ours is the first organization to develop a comprehensive program that provides guidelines for researchers on conducting a thorough literature search. Completion of this module is highly recommended for individuals involved in human subject research. It provides clinical researchers with knowledge of how to locate scientific literature to enable design of scientifically sound research studies and to protect human subjects from harm.